PENGARUH UKURAN PERUSAHAAN DAN DEWAN KOMISARIS INDEPENDEN TERHADAP OPINI AUDIT GOING CONCERN DENGAN FINANCIAL DISTRESS SEBAGIA VARIABEL MODERASI - Yunita Kurnia Shanti; Fernaldy Wahyu Kurniawan (ITB AAS Indonesia Surakarta, 2025)
This study aims to determine the effect of company size and independen board of commissioners on going concern audit opinion. In addition, this study also adds financial distress variables as a moderation, where the regression equation contains an element of interaction (multiplication of two or more independen variables). The type of research used in this study is quantitative research, and the data used in the study is secondary data. The data used in this study are financial reports from energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The results of the study show that company size and independen board of commissioners have a joint effect on going concern audit opinion. Company size has a negative effect on going concern audit opinion. Independen board of commissioners has no effect on going concern audit opinion. Financial distress is able to weaken the effect of company size on going concern audit opinion. Financial distress is unable to moderate the independen board of commissioners on going concern audit opinion.